Litter materials and the incidence of carcass lesions in broilers chickens - Garcia, R G; Paz, Ibiara Correia de Lima Almeida [UNESP]; Caldara, Fabiana Ribeiro [UNESP]; Nääs, I A; Bueno, L G F [UNESP]; Freitas, L W; Graciano, J D; Sim, S (Fundação APINCO de Ciência e Tecnologia Avícolas, 2012)
The aim of this study was to evaluate the effects of different litter materials on litter compaction, broiler feathering and the incidence of carcass lesions. In the experiment, 3240 one-day-old Ross® chicks were selected by sex and distributed according to a completely randomized experimental design in a 2 x 6 factorial arrangement (two sex and six litter materials). The following litter materials were used: wood shavings, rice husks, chopped Napier grass, 50% sugar cane bagasse plus 50% wood shavings, 50% sugar cane bagasse plus 50% rice husks, and pure sugar cane bagasse. Litter compaction was weekly assessed using a penetrometer. on days 21, 35 and 42 of the experimental period, feathering on the back and legs was scored according to a 0 - 10 scale. on day 42, birds were slaughtered and the presence of bruises, scratches and footpad lesions was recorded. Litter material had no effect on bird feathering. Carcass lesions (scratches, bruises and footpad lesions) were influenced by the litter material evaluated. Birds reared on sugarcane bagasse and chopped Napier grass presented more scratches, bruises and footpad lesions than the others. Dermatitis was more evident in birds reared on sugarcane bagasse, chopped Napier grass and the combination of litter materials. It was found that males presented higher incidence of dermatitis and footpad lesions than females. Each litter material presented different compaction degrees, which increased along the experimental period. Sugarcane bagasse, chopped Napier grass and the combination of bedding materials presented the highest degree of compaction, compared with wood shavings and rice husks.
Keywords: Compaction; fathering; quality; substrate